Prebiotic carbohydrates: Effect on physicochemical stability and solubility of algal oil nanoparticles. (15th January 2020) - Wang, Yue; Zheng, Zhaojun; Wang, Kai; Tang, Chuanhui; Liu, Yuanfa; Li, Jinwei
Graphical abstract: Highlights: Algal oil was encapsulated with 98.57% efficiency using a prebiotic system. Nanoparticles with OSA starch, chitosan and inulin showed high oxidative stability. Inulin application improved the water-solubility and wettability of the particles. Abstract: This study aimed at providing a novel approach for improving the physicochemical stability and solubility of algal oil nanocapsules through formation of electrostatic interactions and prebiotic carbohydrates systems composed of: octenyl-succinic anhydride (OSA) starch, OSA/inulin (IN), OSA/maltodextrin (MD), OSA/chitosan (CS), OSA/MD/IN, and OSA/CS/IN. IN, a functional prebiotic modifier, was found to significantly (p < 0.05) decrease emulsion viscosity and particle size, with OSA/CS/IN particles having significantly (p < 0.05) improved water solubility (4.96%) and wettability (749 s) compared to OSA/CS particles. Interestingly, OSA/CS/IN particles had the highest oxidative stability (three times that of bulk oil) and encapsulation efficiency (98.57%). OSA/CS/IN particles were also more hygroscopic than pure OSA particles. Furthermore, scanning electron microscopy (SEM) revealed OSA/CS/IN particles had less wrinkled, smoother surfaces, providing lower air permeability and better protection. Therefore, OSA/CS/IN, as a prebiotic encapsulation system, may lead to the value addition of algal oil.